Isolation and expression analysis of NtCHS6, a new chalcone synthase gene from Nicotiana tabacum - Shuai CHEN; Yin-chao ZHANG; Xu-hao PAN; Yi-ting LI; Li-jie CUI; Feng-yan WU; Mo-ju CAO; Ai-guo YANG; Guang-tang PAN (Journal of Integrative Agriculture, 2017)
Chalcone synthases (CHS, EC 2.3.1.74) are key enzymes that catalyze the first committed step in flavonoid biosynthesis. In this study, we isolated a chalcone synthase, named NtCHS6, from Nicotiana tabacum. This synthase shared high homology with the NSCHSL (Y14507) gene and contained most of the conserved active sites that are in CHS proteins. The phylogenetic analysis suggested that NtCHS6 protein shared a large genetic distance with other Solanaceae CHS proteins and was the most closely-related to an uncharacterized CHS from Solanum lycopersicum. The expression analysis indicated that NtCHS6 was abundantly expressed in leaves, especially in mature leaves. By scrutinizing its upstream promoter sequences, multiple cis-regulatory elements involved in light and drought responsive were detected. Furthermore, NtCHS6 expression decreased significantly under dark treatment and increased significantly under drought stress. Our results suggested that NtCHS6 expression exhibited both light responsiveness and drought responsiveness, and might play important roles in ultraviolet protection and drought tolerance.